2015
DOI: 10.1111/den.12467
|View full text |Cite
|
Sign up to set email alerts
|

Improving the quality of colonoscopy bowel preparation using a smart phone application: A randomized trial

Abstract: Successful cleansing and patient acceptability with the use of SPA were superior to written instructions in outpatients submitted for colonoscopy using 2 L PEG solution plus ascorbic acid.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
74
0
12

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(88 citation statements)
references
References 14 publications
2
74
0
12
Order By: Relevance
“…Five English databases (PubMed, Web of Science, EMBASE, EBSCO, and OVID) and four Chinese databases (the Wanfang Database, Chongqing VIP Database, Chinese National Knowledge Infrastructure, and Chinese Biomedical Database) were searched from their respective inception dates to February 2018. Three categories of search terms were used (‘coloscopy’, ‘bowel preparation’, and ‘smartphone’) and two studies (Kang et al, ; Lorenzo‐Zúñiga, Moreno De Vega, Marín, Barberá, & Boix, ) were identified that had examined the educational effect of a smartphone application on bowel preparation and had included only outpatients; no trial was identified in an inpatient setting. Here, we report the results of the use of mobile applications with inpatients undergoing coloscopy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Five English databases (PubMed, Web of Science, EMBASE, EBSCO, and OVID) and four Chinese databases (the Wanfang Database, Chongqing VIP Database, Chinese National Knowledge Infrastructure, and Chinese Biomedical Database) were searched from their respective inception dates to February 2018. Three categories of search terms were used (‘coloscopy’, ‘bowel preparation’, and ‘smartphone’) and two studies (Kang et al, ; Lorenzo‐Zúñiga, Moreno De Vega, Marín, Barberá, & Boix, ) were identified that had examined the educational effect of a smartphone application on bowel preparation and had included only outpatients; no trial was identified in an inpatient setting. Here, we report the results of the use of mobile applications with inpatients undergoing coloscopy.…”
Section: Introductionmentioning
confidence: 99%
“…With the development of technology, mobile applications have made receiving information any time and any place much easier than it was with traditional educational interventions. By providing an easily accessible and interactive channel of communication between patients and information providers, these applications have the potential to affect public health (Kang et al, 2016) Three categories of search terms were used ('coloscopy', 'bowel preparation', and 'smartphone') and two studies (Kang et al, 2016;Lorenzo-Zúñiga, Moreno De Vega, Marín, Barberá, & Boix, 2015) were identified that had examined the educational effect of a smartphone application on bowel preparation and had included only outpatients; no trial was identified in an inpatient setting. Here, we report the results of the use of mobile applications with inpatients undergoing coloscopy.…”
Section: Introductionmentioning
confidence: 99%
“…Another prospective RCT reported that a new smart phone app was created for BP, with the functions of providing various educational tools (e.g. written text, visual aids and educational video) and timed alerts that remind patients of all steps to be taken during BP.…”
Section: Enhanced Education For Making Instructions Easily Accessiblementioning
confidence: 99%
“…The second category, including the short message service (SMS) and telephone, has the main advantages of reminding the patients. The third contains a smart phone application (app), which makes instructions easily accessible (Table ).…”
Section: Introductionmentioning
confidence: 99%
“…ABD'de uzun dönemli polipek-turmakta ve ekonomik yükü artırmaktadır. Bağırsak hazırlığı ilaçlarının hastalar tarafından tolere edilememesi, bulantı, ağrı gibi şikayetlere yol açması, işlem öncesinde bilgilendirmedeki eksiklikler gibi çeşitli faktörler bağırsak hazırlığına uyumu olumsuz yönde etkilemektedir (12,14). Bağırsak hazırlığının maliyet, güvenlik, tolerasyon, komorbidite, hastanın tercihleri ve genel sağlık durumu göz önünde bulundurularak bireyselleştirilmesi gerekmektedir (15).…”
unclassified